Swing control for a three-link brachiation robot based on sliding-mode control on irregularly distributed bars - Z. Lu (Copernicus Publications, 2021)
The bionic-gibbon robot is a popular bionic robot. The bionic-gibbon robot can imitate a gibbon in completing brachiation motion between branches. With nonlinear and underactuated properties, the robot has important research value. This paper designs a type of bionic-gibbon robot with three links and two grippers. To simplify the controller, a plane control model is proposed, and its dynamic model is established. The control strategy in this paper divides the brachiation motion into several processes: adjust posture, open the gripper, the swing process and close the gripper. Based on sliding-mode control (SMC), the control method for the swing process is designed. The target position of the brachiation motion is set as the origin of the sliding-mode surface. In a finite time, the robot will reach the target position along the approach rate we adopt. In this way, the robot can complete the desired brachiation motion only by setting the position parameters of the target bar. We perform some simulations in ROS-Gazebo. The simulation results show that the bionic-gibbon robot can complete continuous brachiation motion on irregularly distributed bars. The sliding-mode control and the three-link structure significantly improve the robustness and swing efficiency of the bionic-gibbon robot.